Interest Rate Pass-Through in Pakistan: Evidence from the Asymmetric Co-integration Approach - Farrukh Mahmood (NUST Journal of Social Sciences and Humanities, 2021)
This study examines the asymmetry of interest rate pass-through between wholesale (KIBOR) and retail interest rates (Deposit and Lending rate) for Pakistan, by using the asymmetric threshold co-integration proposed by Enders & Sikles (2001) and EC-EGARCH-M model proposed by Wang & Lee (2009). Empirical results of threshold co-integration test confirm that asymmetric relation exists between wholesale and retail interest rates, and hence the rate of pass-through is incomplete. Furthermore, in the long-run, retail interest rates are rigid towards the downwards adjustment, and hence there is an upward adjustment in error correction mechanism.